1991
DOI: 10.1159/000288531
|View full text |Cite
|
Sign up to set email alerts
|

Therapy Outcome of Two Treatment Models for Bulimia nervosa: Preliminary Results of a Controlled Study

Abstract: Beyond the reduction of the core symptoms, different modification patterns are expected due to differing emphases in two alternative types of treatment for bulimia nervosa: inpatient analytic and outpatient systemic therapy. The initial results of a study with a waiting-list control group are reported. Eating disorders of the bulimic women definitely improved in both therapy groups, the results for the inpatient group (n = 27) indicate a basic change in the attitude towards eating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The first report of a group intervention for this disorder was by BoskindLodahl and White in 1978. Since then, a variety of different approaches have been suggested in the literature (Lacey, 1983;Connors, Johnson, & Stuckey, 1984;Yates & Sambrailo, 1984;Kirkley, Schneider, Agras, & Bachman, 1985;Ordman & Kirschenbaum, 1985;Lee and Rush, 1986;Wolchik, Weiss, & Katzman, 1986;Wilson, Rossiter, Kleifeld, & Lindholm, 1986;Fairburn, Kirk, O'Connor, & Cooper, 1986;Laessle, Waadt, & Pirke, 1987;Leitenberg, Rosen, Gross, Nudelman, & Varal, 1988;Freeman, Barry, Dunkeld-Turnbull, & Henderson, 1988;Agras, Schneider, Arnow, Raeburn, & Telch, 1989;Mitchell et al, 1990;Liedtke et al, 1991;Hsu, 1991;Agras et al, 1992;Garner et al, 1993). This section will discuss the controlled psychotherapy studies published or presented to date.…”
Section: Psyc Hoth Erapy Stu DI Esmentioning
confidence: 99%
See 2 more Smart Citations
“…The first report of a group intervention for this disorder was by BoskindLodahl and White in 1978. Since then, a variety of different approaches have been suggested in the literature (Lacey, 1983;Connors, Johnson, & Stuckey, 1984;Yates & Sambrailo, 1984;Kirkley, Schneider, Agras, & Bachman, 1985;Ordman & Kirschenbaum, 1985;Lee and Rush, 1986;Wolchik, Weiss, & Katzman, 1986;Wilson, Rossiter, Kleifeld, & Lindholm, 1986;Fairburn, Kirk, O'Connor, & Cooper, 1986;Laessle, Waadt, & Pirke, 1987;Leitenberg, Rosen, Gross, Nudelman, & Varal, 1988;Freeman, Barry, Dunkeld-Turnbull, & Henderson, 1988;Agras, Schneider, Arnow, Raeburn, & Telch, 1989;Mitchell et al, 1990;Liedtke et al, 1991;Hsu, 1991;Agras et al, 1992;Garner et al, 1993). This section will discuss the controlled psychotherapy studies published or presented to date.…”
Section: Psyc Hoth Erapy Stu DI Esmentioning
confidence: 99%
“…This interpersonal psychotherapy approach was originally developed for the treatment of depression by Merman, Weissman, Rounsaville, and Chevron (1984). Garner (unpublished manuscript) compared psychodynamic therapy with standard cognitivebehavioral therapy, and Liedtke et al (1991), in a study still in progress, is comparing an inpatient psychoanalytic approach to outpatient 12-month long "systemic" therapy. Our group (Mitchell et al, in press) recently completed a study that manipulated intensity and emphasis on abstinence in a group cognitive-behavioral therapy model.…”
Section: Psyc Hoth Erapy Stu DI Esmentioning
confidence: 99%
See 1 more Smart Citation
“…The results also indicate that family therapy alone is not sufficient to treat bulimia nervosa. Similarly, preliminary findings of a controlled study which compared 2 months of inpatient psychoanalytic group therapy, 1 year of systemic family therapy, and a waiting-list control group (Liedtke et al, 1991) indicated that significant changes occurred in both treatments. However, methodological flaws in this study suggest that caution be exercised in the interpretation of their findings.…”
Section: Family Therapymentioning
confidence: 98%
“…In this sense, I believe that many of Hellmuth Freyberger's contributions in volumes [2,3,10,11,12,15] and journals [5,13,14,15,16,17,18,19,20] have still to be fully appreciated with their unique blend of introspection and dialogue as scientific instruments. Hellmuth Freyberger believed in psychosomatic medicine as the cumulative experience of the psychosomatic community, the legacy of those who have gone before and those who live today.…”
mentioning
confidence: 99%